Perancangan Strategi Perawatan dengan Reliability Center Maintenance di PT. X - Tan Didik Wardoyo Tanusi; Siana Halim (Jurnal Titra, 2014)
In 2013 PT. X experienced downtime frequently. Some of the failures that lead to the downtime are broken shaft helical gear, broken fan funnel axle, broken long axle; broken worm, worn down drig laker, and worn down blade. The maintenance strategy in the company has not covered all failures specifically. Thus, this project is Reliability Centered Maintenance Method (RCM) with Dempster-Shafer approach which covers those failures. It was found that condition based maintenance is the best strategy for maintaining each failure. This strategy is easily to apply since the company has implemented autonomous and planned maintenance.